2005
DOI: 10.1007/s11136-004-0801-3
|View full text |Cite
|
Sign up to set email alerts
|

Health-related and overall quality of life of patients with chronic hip and knee complaints in general practice

Abstract: Background: Information about quality of life of patients with chronic hip or knee complaints in general practice is scarce. This study describes the health-related and overall quality of life (HRQL) of these complaints. Methods: Data were obtained from a cohort study in general practice. HRQL at three months follow-up was analysed. HRQL was measured as: symptoms, physical, psychological and social functioning, and general health perceptions, using the Western Ontario and McMaster Universities osteoarthritis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
3
17
1
1
Order By: Relevance
“…The SF-36 RS domain showed the largest improvement after rehabilitation; this finding contradicted the results observed in other studies (14,19,23), with some studies reporting high scores for that domain before rehabilitation (1,12). Generally, hip OA patients receive low scores for the SF-36 BP domain (1,12,14,15,(19)(20)(21)(22)(23)(24), which was in accordance with our results; thus, after rehabilitation, this was one of the domains that showed moderate improvement in our patients, although other studies reported that this domain showed the greatest improvement (14-16, 20, 23, 25). A Cochrane review from 2014 (26) included nine studies (549 patients) and showed that exercise therapy reduces pain and improves physical function immediately after treatment.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The SF-36 RS domain showed the largest improvement after rehabilitation; this finding contradicted the results observed in other studies (14,19,23), with some studies reporting high scores for that domain before rehabilitation (1,12). Generally, hip OA patients receive low scores for the SF-36 BP domain (1,12,14,15,(19)(20)(21)(22)(23)(24), which was in accordance with our results; thus, after rehabilitation, this was one of the domains that showed moderate improvement in our patients, although other studies reported that this domain showed the greatest improvement (14-16, 20, 23, 25). A Cochrane review from 2014 (26) included nine studies (549 patients) and showed that exercise therapy reduces pain and improves physical function immediately after treatment.…”
Section: Resultssupporting
confidence: 91%
“…In fact, the average SF-36 RP domain score reported in this study was lower than that recorded in other studies (12,14,(20)(21)(22)(23), while Krauss et al reported the highest score for this domain (5). After rehabilitation, the SF-36 RP domain showed the greatest improvement, followed by the RE domain.…”
Section: Resultscontrasting
confidence: 83%
“…Previous studies have compared disease-specific and generic instruments [3][4][5]. Disease-specific measures are traditionally used in longitudinal studies or in clinical trials to detect progressive changes after medical or surgical interventions, particularly changes in pain and physical functions [6,7]. The Harris Hip Score (HHS), a disease-specific HRQoL instrument, is widely used by physicians to assess physical function and pain relief in patients with hip disease [8].…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that most patients still had their knee pain after 1 year. Because knee pain has a substantial impact on individuals' lives (48) and on their use of primary health care resources (49), the need to identify practical and effective means of reducing this burden should be a priority for research and development in primary care. Future research should focus not only on physical interventions, but also on psychological interventions.…”
mentioning
confidence: 99%